1997
DOI: 10.1002/chp.4750170304
|View full text |Cite
|
Sign up to set email alerts
|

Patient education materials: Physician perception of their role and usefulness

Abstract: This paper discusses the results of a study done to determine physician use ofpatient education material and the types of material that physicians found most useful to them. A random sample of Canadian physicians was studied using a mailed questionnaire. The majority of physicians indicated that they used patient education materials. Information produced by pharmaceutical companies and voluntary organizations was most useful. Physicians used this material to facilitate patient compliance and to reinforce infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
1998
1998

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Finally, we were concerned about the availability of health education and the ability to identify gaps in education program offerings. A study of Canadian physicians suggested that more than one-half surveyed use patient education materials, primarily to increase patient adherence (10). However, we do not know if American physicians behave similarly.…”
Section: Introductionmentioning
confidence: 84%
“…Finally, we were concerned about the availability of health education and the ability to identify gaps in education program offerings. A study of Canadian physicians suggested that more than one-half surveyed use patient education materials, primarily to increase patient adherence (10). However, we do not know if American physicians behave similarly.…”
Section: Introductionmentioning
confidence: 84%